The Relationship Between Self-Efficacy and Student Involvement in Plane Structure Material in Elementary Schools - Ido Bijak Laksana; Siti Masula; surayanah (Universitas Pendidikan Ganesha, 2025)
This study was motivated by the essential role of academic self-efficacy as a psychological factor that contributes to students’ engagement in the learning process. The purpose of this research was to analyze the relationship between self-efficacy and student engagement. This quantitative non-experimental study employed a correlational design and involved elementary school students as research subjects. Data were collected using validated and reliable questionnaires measuring self-efficacy and student engagement. Data analysis was performed using Pearson’s correlation test through the JASP software. The results showed that students’ self-efficacy levels fell into low, medium, and high categories at 17%, 63%, and 20%, respectively, while student engagement levels were categorized as low, medium, and high at 13%, 69%, and 19%. The correlation analysis confirmed a significant relationship between self-efficacy and student engagement. These findings indicate that self-efficacy plays an important role in enhancing students’ involvement in learning activities. The study implies the need for instructional strategies that strengthen students’ academic confidence to foster greater participation and engagement in classroom learning.